Determinants of the Sensory Quality of Półgęsek in Relation to Volatile Compounds and Chemical Composition - Nowicka Katarzyna; Jaworska Danuta; Przybylski Wiesław; Górska Ewa; Tambor Krzysztof; Półtorak Andrzej (Polish Journal of Food and Nutrition Sciences)
The objective of this study was to determine the sensory quality of a specific Polish traditional product made from cured and then smoked goose meat (półgęsek) in relation to its volatile compounds and chemical composition. In general, the examined samples contained 66.2% water, 12.2% fat, 17.9% protein, 1.8% connective tissue, and 2.3% NaCl. Moreover, 47 volatile compounds were identified and quantified. The typical decomposition products derived from lipid oxidation, amino acid degradation, carbohydrate fermentation and microbial esterification were the main volatiles detected in all the samples. The volatiles generated by the smoking process and the ones originating from spices were also observed. The results of the sensory evaluation indicated that all the samples of the analyzed products were characterized by a high overall quality. Results of the Principal Component Analysis (PCA) showed, however, that specific groups of products have their own unique sensory profile. Additionally, the sensory analysis confirmed the significant role of the chemical composition and volatile compounds in the development of the overall quality of półgęsek.